Challenges in Menstrual Hygiene Practices among Urban and Rural Women (Aged 15-45 Years) of District Pali in Western Rajasthan - Latika Nath Sinha; Sanjay Choudhary; Bal Gopal Bhati; Rakesh Mewara; Amandeep Semwal (Indian Association of Preventive and Social Medicine, 2021)
Introduction: In India, even today regressive socio-cultural norms pertaining to menstruation continue to thrive in many parts. The government in Rajasthan has been distributing sanitary napkins to girls in the age group 10-19 years through the Education & ICDS department since 2018. This study assesses utilization and acceptance of the sanitary pads distributed frees of cost among adolescents and at a nominal rate to women and identifies the challenges in observing menstrual hygiene practices in semi arid areas. Method: A cross-sectional study was conducted among women aged 15-45 years in six urban wards and six sub- centre villages under the Rural Health and training Centre(RHTC) Gundoj. Keeping power of study at 80% adding the 10% non-response, 50% prevalence for hygienic menstrual practices, a sample size of 384 participants was taken, 192 each from rural and urban areas with 50% of the participants being school going girls. Results: Among school going participants 184 ( 95.8%) in urban areas and 169(88%) were utilizing the free sanitary pads distributed in schools, rest used locally purchased "red cloth". Average level of hygiene practices was comparatively more among urban participants 173(90%) than rural women 77(40.1%) (p value<0.05).During menstruation performing religious activities, doing idol worship, eating and drinking water with family was taboo among 92% of both urban and rural respondents. Conclusion: Distribution of sanitary pads in schools is a successful intervention in Pali District. However, knowledge of healthy menstrual hygiene practices was low (23%) among rural women. Disposal of used pads and attitude towards social taboos need to be addressed in the rural areas of the district with better convergence between Education, ICDS and Health department for advocacy of healthy menstrual hygiene practices.